0139 Occupational exposure to chlorinated solvents and lung cancer: results from the ICARE study. (23rd June 2014) - Mattei, Francesca; Guida, Florence; Sanchez, Marie; Cénée, Sylvie; Févotte, Joëlle; Luce, Daniele; Stücker, Isabelle
Abstract : Objectives: We aimed to investigate the role of occupational exposure to chlorinated solvents in the aetiology of lung cancer. Method: ICARE is a multicenter population-based case-control study conducted in France between 2001 and 2006. Information on subjects lifelong work history was collected by face to face interviews using standardised questionnaires. Occupational exposures were assessed using job-exposure matrices (JEM) relative to five chlorinated solvents including trichloroethylene (TCE), methylene chloride, perchloroethylene (PER), chloroform and carbon tetrachloride. Solvents were studied separately and since overlapping among exposures analyses for combined solvents exposure were performed. In the questionnaire, subjects also had to report if they were exposed to TCE or other substances (PER was among them). Odds ratios (ORs) were computed using unconditional logistic regression models adjusted for classical risk factors. Results: A total of 2926 cases (2276 men and 650 women) and 3555 controls (2780 men and 775 women) were included. A statistically significant positive association for lung cancer risk was observed in both men (OR 1.47, 95% CI: 1.00–2.17) and in women (OR 3.86, 95% CI: 1.36 -11.01) exposed to PER combined with TCE and/or methylene chloride. In contrast, no statistically significant associations were found for TCE or other solvent combinations. Finally for subjects, who reported the exposure to PER, the ORs were 3.25 (95% CI: 1.23, 8.59) and 3.12 (95% CI: 0.50, 19.28) among men and women respectively. Conclusions: The results of this study suggest that PER alone or in combination with TCE and/or methylene chloride may increase the risk of lung cancer.